Character Education Integration in Distance Learning System Based on Multiple Intelligence Theory: Case Study at SMKN 2 Malang - Admaja Dwi Herlambang; Qonita Rahmawati; Wibisono Sukmo Wardhono (Elinvo (Electronics, Informatics, and Vocational Education), 2022)
This study aims to determine how the strategies carried out by Public Vocational High Schools in Malang City, Indonesia, implement character education in the distance learning system. This research occurred at the 2nd  PublicVocational High School (SMKN 2 Malang), Computer and Network Engineering Department. The design of this research is an interactive qualitative analysis model, i.e., reduction, data presentation, and deduction. Data collection techniques are in-depth interviews, observation, and documentation for six months. Data documentation consists of diagnostic tests, Learning Management System (LMS) screenshots, and discipline time records during distance learning. This study shows that from knowledge aspect, teachers can understand students' character well so that the application of multiple intelligence strategies by utilizing diagnostic tests and LMS can be realized. However, the implementation of character education often experiences problems or lacks student technical support, so its implementation is carried out consistently by incorporating character values in every learning activity. This study recommends that observation activities be carried out when learning activities need to be optimized with synchronous learning activities.